Mapping the Problems in Village Financial Management (VFM) - Tri Utami; Agung Nugroho Jati; Cahaya Nugrahani; Tri Wahyuni (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
Planning is the first stage in Village Financial Management (VFM). Identifying people’s problems is vital in VFM. This study investigates the problems in VFM, especially identifying issues based on sector, sub-sectors, and activities. The subject is 52 Heads of Village Planners. Subjects ask to write the problems in the village. The data is analyzed by comparing the issues and entering them into appropriate sectors. This study shows the Village Development Implementation has significant education, health, and residential issues. Village Community Empowerment’s main issues are the Agriculture and Livestock Sub-Sector. Village Government Implementation has potential problems related to civil registration, statistics, population archives, governance, planning, finance, and reporting. The Disaster Management, Emergency, and Urgent Sectors have problems, including limited social funds and direct cash assistance distribution. Finally, the Village Community Development has the most issue consisting of family welfare development programs, fostering youth organization, and lack of training in cultural groups.